Application of Restorative Justice to the Crime of Sexual Violence against Women - Ganen Seknun; Hadi Tuasikal; R.S. Rakia, A. Sakti; Nini Nurouzi (JUSTISI, 2024)
This research highlights the background of Indonesia as a state of law, where state power is regulated by law to achieve legal order. However, the implementation of laws to protect women from violence still poses weaknesses that affect the sense of justice and impunity for perpetrators. As an alternative solution, the Restorative Justice approach is proposed to resolve acts of sexual violence by involving victims and perpetrators in dialogue and joint recovery, in accordance with the principle of consensus. This research uses the normative juridical method by analyzing relevant regulations and literature as well as conducting interviews at the Teluk Bitung District Police. It was found that the Restorative Justice approach can be a more inclusive and restorative alternative for victims and perpetrators of sexual violence. However, to implement it effectively, certain conditions need to be met, including admission of guilt, consent of the victim and perpetrator, and support from the police or prosecutor's office. The results show that this approach has the potential to provide a fairer resolution and have a positive impact on efforts to prevent and respond to violence against women in Indonesia.